Emerging role for pharmacogenomics in HIV research in Africa - Zhou, Danai Tavonga; Mudhluli, Taona Emmah; Madhombiro, Munyaradzi; Nyamhunga, Albert; Matekaire-Chirimo, Ratidzo; Mudzviti, Tinashe; Manasa, Justen; Ma, Qing; Maponga, Charles Chiedza; Morse, Gene D (Future Science Group, 2022)
Pharmacogenomics is the study of genes that affect response to drugs. It combines pharmacological and genomics principles, to predict effectiveness and safety of therapeutic agents. This is, in part, because drug response and toxicity are influenced by pharmacokinetic factors that result in interindividual variability in drug-metabolizing enzymes and membrane transporters [1]. Variants of relevance include members of the cytochrome P450 (CYP450) family. Genetic variation of CYP450 genes alone is estimated to influence a quarter of all drug therapies [2]. Pharmacogenomic research is thus imperative for development and function of drugs, including antiretrovirals, anticancer medicines, antibiotics and lipid-lowering therapies, among others. Pharmacogenomics research in Africa is especially valuable in the context of high genetic variability [1,3], high HIV burden and growing noncommunicable disease incidence. A recent publication on whole genome sequencing in hundreds of people from across Africa revealed an unexpectedly large number of new single-nucleotide variants [4]. Yet, less than a quarter of participants in current genomics (and by extension pharmacogenomics) research are non-Europeans, leaving out a large majority of human genetic variants [5]. The need for more inclusive genetic research further attests to the emerging role for pharmacogenomic studies across Africa.